Hubungan Antara Mikroalbuminuria dan Skor SOFA pada Pasien Sepsis yang Dirawat di ICU RSUP Dr Sardjito - Sulistiyantoro, Antonius Catur; Widodo, Untung; Jufan, Akhmad Yun (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Background: Sepsis causes release of inflammatory mediator to circulation. The inflammatory molecules and oxidative stress increase the capilar permeability include the glomerular renalis. An early event is the loss of barrier integrity leading to systemic capillary leakage. The glomerular manifestation of this increased permeability is increased excretion of albumin in the urine. Microalbuminuria, defined as 30–300 mg/day of albumin excretion in the urine, occurs rapidly after an acute inflammatory insult such as sepsis. SOFA scoreis one of parameter to asses the degree of organ dysfunction severity.Purpose: The purpose of this study was to determine the correlation between microalbuminuria and SOFA score in patient with sepsis in ICU Dr. Sardjito Government General Hospital.Methods: This observational study was conducted in ICU Dr. Sardjito Government General Hospital between January-July 2019. Inclusion criteria were all patients with sepsis admited to ICU (≥18 years old), exclusion criteria were patient with diabetic mellitus, anuria, chronic kidney disease, pregnant, urological trauma, nephrotic syndrome, urinary tract infection. urine samples were collected per 24 hour (Day-1st), 48 hour (Day-2nd) and 72 hour (Day-3st). The microalbuminuria was measured in hospital laboratory. The SOFA score evaluated every day. The correlation between SOFA score with microalbuminuria was analyzed with SPSS.Result: Total 35 subject included, 20 subject excluded, 1 subject dropout. The study included 57,1% male and 42,9% female, mean of SOFA score were 9,4 ± 3,4, mean of microalbuminuria were 132 ± 75,2 mg/l. Subject with septic shock were 42,9% and all of subject required mechanical ventilation. Mortality rate were 50%, the major infection sourced was respiratory tract (42,9%), and the major bacteria was Acinebacter baumanii. The mean of SOFA score in survivor subject were 6,43 ± 2,80 and not survivor were 10,34 ± 3,00, the microalbuminuria in survivor subject were 82,10 ± 70,73 mg/l and not survivor were 167,71 ± 46,81 mg/l. There was positive correlation between microalbuminuria and SOFA score with strength correlation r: 0,627, p: 0,016. SOFA score >7 had risk 16 times to die, and microalbuminuria >156,35 had prognostic risk 36 times to die.Conclusion: There was positive correlation between microalbuminuria level and SOFA score in septic patients in ICU Dr. Sardjito Government General Hospital.